Intravitreal Bevacizumab for the Treatment of Subfoveal Choroidal Neovascularization Secondary to Age Related Macular Degeneration - Zaheer-ud-Din Aqil Qazi, Muhammad Naeem Azhar,Muhammad Ali Haider , HaroonTayyab, Arslan Ahmed (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the mean percentage decrease in central macular thickness with intravitreal Bevacizumab for the treatment of subfoveal Choroidal Neovascularization secondary to Age related Macular Degeneration. Material and Methods: From September 2009 to March 2010, thirty five diagnosed patients of subfoveal choroidal neovascularization secondary to age related macular degeneration were taken from out-door patient department of Layton Rahmatulla Benevolent Trust Eye and Cancer Hospital, Lahore. After taking aseptic measures intravitreal Bevacizumab (Avastin) injection (1.25 mg/ 0.05 ml) was injected through pars plana. Post injections follow up was done by central macular thickness (in ?m) measured by Optical coherence tomography at 4th week, 8th week and finally at 12th week. Results: Thirty five eyes of 35 consecutive patients received the three injections of intravitreal Bevacizumab 1.25 mg / 0.05 ml, each injection 4 weeks apart and all patients had 3 months of follow up. Mean central macular thickness ± SD decreased from 308.86 ± 39.13 ?m at baseline to 228 ± 17.62 ?m at 12th week. In our study mean percentage decrease in central macular thickness was 26.18% at 12th week after three intravitreal Bevacizumab injections. Conclusion: Intravitreal Bevacizumab injection results in short term decrease in central macular thickness to normal or near-normal levels in eyes with choroidal neovascularization secondary to age-related macular degeneration.